The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1177/0193723599233004
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Differences in Sport Participation as a Function of Self-Schema

Abstract: The present investigation studied the influence of race and gender on sport and physical activity choices by regarding specific sport and physical activities as appropriate for participation or self-defining for race and gender groups. The study was designed to confirm the existence of self-schemata for sport and physical activities. A computer-generated instrument was employed to assess the existence and strength of self-schemata. Results of logistic regression analysis suggest that self-schemata for particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…As argued by Eccles and her colleagues Eccles & Harold, 1991;Wigfield, Eccles, & Rodriguez, 1998), gender role socialization and gender intensification at puberty may have influenced the development of men's and women's competence beliefs and expectations for success. As a result, men and women have higher levels of perceived competence and expectations for success when the activity is perceived as gender-typical (Harrison et al, 1999;Lee et al, 1999;Lirgg et al, 1996). Men in our study tended to rate natural ability as more influential for activities that were gender-typical for them, but the same was not true for women.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…As argued by Eccles and her colleagues Eccles & Harold, 1991;Wigfield, Eccles, & Rodriguez, 1998), gender role socialization and gender intensification at puberty may have influenced the development of men's and women's competence beliefs and expectations for success. As a result, men and women have higher levels of perceived competence and expectations for success when the activity is perceived as gender-typical (Harrison et al, 1999;Lee et al, 1999;Lirgg et al, 1996). Men in our study tended to rate natural ability as more influential for activities that were gender-typical for them, but the same was not true for women.…”
Section: Discussioncontrasting
confidence: 51%
“…Activities associated with strength and power such as football, baseball, basketball, and weight lifting are usually perceived as masculine activities, whereas activities such as gymnastics, dance, and aerobics are considered feminine activities (Eder & Parker, 1987;Weinberg, 1997). These views have limited women's involvement in physical activity and sports, especially in vigorous activities that are traditionally male-dominant (Harrison, Lee, & Belcher, 1999). As a consequence, men and women have particular expectations about their capabilities in various sports, and their subsequent attributions are likely to be affected by those expectations (Biddle, 1993;Jacobs, Lanza, Osgood, Eccles, & Wigfield, 2002).…”
mentioning
confidence: 99%
“…Institutions should consider developing or supporting youth sport development programs for nonrevenue sports targeted at minorities, in the same way they do for similar programs focused on academic development. There are challenges associated with self-segregation of athletes into certain sports (Harrison, Lee, and Belcher, 1999). Yet a number of programs have proven to be successful, such as the National Youth Sports Program, Lacrosse for Life, and USA Swimming.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Different investigations have demonstrated that the gender variable has a determining influence on the social structure of sport (Harrison, Lee & Belcher, 1999;Dunning, 1999;Puig & Soler, 2004;Ottogalli-Mozzacavallo, 2004). From this literature, we should emphasize two essential pieces of evidence.…”
Section: Introductionmentioning
confidence: 99%